Clinical presentation and genetic variants in patients with autoinflammatory diseases: results from the German GARROD registry - Blank, Norbert; Kötter, Ina; Schmalzing, Marc; Rech, Jürgen; Krause, Karoline; Köhler, Birgit; Kaudewitz, Dorothee; Nitschke, Martin; Haas, Christian S.; Lorenz, Hanns-Martin; Krusche, Martin (Rheumatology international, 2023)
To investigate clinical symptoms and genetic variants in patients from the German anti-IL-1 registry for autoinflammatory orphan diseases (GARROD) between 2013 and 2022. Multicentre, retrospective analysis of demographic, clinical and genetic data of patients with autoinflammatory diseases (AID) who received anti-IL-1 targeted therapy. The cohort comprised 152 patients with familial Mediterranean fever (FMF; n = 71), cryopyrin-associated periodic syndromes (CAPS; n = 43), TNF-receptor associated periodic syndrome (TRAPS; n = 19), mevalonate kinase deficiency (MKD; n = 3) and unclassified AID (uAID; n = 16). Inflammatory attacks started in 61.2% of the patients before the age of 18 years. The delay between the first AID attack and anti-IL-1 therapy was 17.8 years. Monogenetic AIDs were diagnosed by clinical symptoms. Genetic analyses confirmed the diagnosis in 87.3% of patients with FMF, 65.2% with CAPS and 94.8% with TRAPS. Among this group, heterozygous MEFV variants and variants of unknown significance (VUS) were detected in 22.5% of patients with FMF, 51.2% with CAPS and 47.4% with TRAPS. Patients with VUS were older at disease onset which is consistent with a milder phenotype. Twenty-four patients had secondary AA amyloidosis (AA) at initiation of anti-IL-1 therapy. The mean age of these patients was 16.4 years at their first attack and 44.9 years at the time of AA diagnosis. Turkish-Armenian ancestry correlated with MEFV variants and higher FMF disease activity compared to German ancestry. Molecular genetic analyses should substantiate the clinical diagnosis of a monogenetic AID. Our data support the concept of variable penetrance of VUS which can be associated with late-onset AID.